Sistem Otomasi Penggantian Air Menggunakan Sensor dan Mikrocontroller - Muhamad Sidik (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
This research aims to ease the work of freshwater ornamental fish breeders who use aquariums or can also be implemented in ordinary ponds. Usually cultivators work using extra (manual) labor to be more effective using tools. This research is a type of development research with reference to the R & D (Research And Development) method. The results of the study show that, in testing the tool can function properly. All components and sensors can function with 85% accuracy. Thus, Aquarium Water Replacement Automation Using Turbidity and Arduino Uno is suitable for use by cultivators.